Building Students' Interest in Learning During a Pandemic Through a Program for Implementing Educational Policies During an Emergency Period for the Spread of Covid-19 - Asihkha, Nur (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Building student interest in learning is one way so that learning objectives can be achieved. Students who have a high interest in learning will make it easier to understand the learning material. Several programs that can increase the interest of students during the pandemic include 1) Interactive and Non-Interactive Online Learning 2) Life Skills Education 3) Learning in accordance with Student Interests and Conditions 4) Qualitative Assignment Assessment. Can be applied through entertainment methods, creative applications and lesson plans that involve students. With the involvement of teachers in the student learning process will realize the learning objectives to be achieved